PENGARUH PENDAPATAN ASLI DAERAH DAN DANA OTONOMI KHUSUS TERHADAP INDEKS PEMBANGUNAN MANUSIA MELALUI BELANJA MODAL SEBAGAI VARIABEL MODERATING - Nanda, Rizky; Moh. Khusaini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Humans are any region’s main source of development. Therefore, improvement on their quality, which is measured through Human Development Index (HDI), is necessary. Cities and regencies in Papua city are high in discrepancy concerning the said index. Therefore, the roles of the government as the policy makers are crucial. The objective of this research is to identify the effects of local own-source revenue and special autonomy funds on HDI with capital expenditures as the moderating variable. This research uses secondary data from 29 regencies and cities in Papua province, from 2017 to 2021 and was analyzed through panel data regression with interaction. The hypothesis testing and the model feasibility assessment were conducted using t-test, F-test, and coefficient of determination test. This study finds that local own-source revenue, special autonomy funds, and capital expenditures negatively and significantly influence HDI. Furthermore, capital expenditures as the moderating variable were found to strengthen the partial effects of local own-source revenue and special autonomy funds to HDI. Finally, this research is expected to serve as evaluation material and reference for the government in its policy-making processes and to enrich the treasury of knowledge in financial literacy.